1972
DOI: 10.1042/bj1270705
|View full text |Cite
|
Sign up to set email alerts
|

Oestradiol inhibits collagen breakdown in the involuting rat uterus

Abstract: 1. The earlier observation (Woessner, 1969) of oestradiol inhibition of collagen breakdown is confirmed and extended. Administration of 100mug of oestradiol-17beta/day to parturient rats strongly inhibits the loss of collagen from the involuting uterus. Three experiments show that this effect is due to an inhibition of collagen degradation rather than to a stimulation of collagen synthesis. 2. Uterine collagen was labelled with hydroxy[(14)C]-proline by the administration of [(14)C]proline near the end of preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1973
1973
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…The effects of estrogen on uterine collagen metabolism have been studied. Ryan & Woessner (1972) showed that administration of E 2 to parturient rats strongly inhibits the loss of collagen from the involuting uterus, and found that this effect is due to inhibition of collagen degradation rather than stimulation of collagen synthesis. Furthermore, Woessner (1979) found that injection with E 2 causes a decrease in uterine collagenase activity that is correlated with the rate of collagen breakdown.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of estrogen on uterine collagen metabolism have been studied. Ryan & Woessner (1972) showed that administration of E 2 to parturient rats strongly inhibits the loss of collagen from the involuting uterus, and found that this effect is due to inhibition of collagen degradation rather than stimulation of collagen synthesis. Furthermore, Woessner (1979) found that injection with E 2 causes a decrease in uterine collagenase activity that is correlated with the rate of collagen breakdown.…”
Section: Discussionmentioning
confidence: 99%
“…In the procedure of McCroskery et al (1975), al-CB7 linked to agarose was used as a ligand and was shown to have greater specificity for collagenase than did collagen, which also bound other proteins. This technique exploits a property of coUagenases which is of considerable importance in devising a means of extracting coUagenases from tissues and in evaluating the tissue levels of active enzymes, i.e., the tendency of the enzyme to bind rather tightly to collagen fibrils (Ryan and Woessner, 1971;Pardo and Pérez-Tamayo, 1975;Weeks et al, 1976). Binding of collagenase to extracellular collagen Ohlsson and Olsson (1973) and Lazarus (1973).…”
Section: Purification and Propertiesmentioning
confidence: 98%
“…As a result, collagenase-produced collagen fragments would be expected to lose the protection afforded by the triple-helical conformation of the native molecule and thereby become susceptible to a variety of extracellular proteases. A number of neutral proteases such as those in skin (Lazarus and Barrett, 1974), rheumatoid synovial tissue Steven et al, 1975), uterus (Ryan and Woessner, 1972), and tadpole skin (Harper and Gross, 1970) are capable of degrading gelatin to lower molecular weight fragments. Some neutral proteases such as the synovial fluid enzyme described by Steven et al (1975) and neutrophil elastase and cathepsin B (Starkey et al, 1977) may assist collagenases by cleaving collagen fibrils in telopeptide regions that are normally involved in the formation of intermolecular cross-links (see Section VI).…”
Section: Additional Enzymatic Degradationmentioning
confidence: 99%
“…The liver enzyme was shown to be distinct from the other known cathepsins. Recent studies on uterine involution have shown that oestradiol, which inhibits collagenolysis in vivo, has no effect on the breakdown of collagen in witro [8].The present investigation has been undertaken to compare the effect of involution on the level of collagenolytic activity with the change in acid proteinase activity. A study with activators and inhibitors was made to distinguish the separate identities of these two enzyme activities.…”
mentioning
confidence: 99%